2013
DOI: 10.7567/apex.6.044001
|View full text |Cite
|
Sign up to set email alerts
|

Record Combination of Power-Gain Cut-Off Frequency and Three-Terminal Breakdown Voltage for GaN-on-Silicon Devices

Abstract: We report on an emerging GaN double heterostructure grown on silicon, which enables the simultaneous achievement of high breakdown voltage and high frequency performance. The use of an AlN barrier layer capped by an in situ SiN layer, and the introduction of an AlGaN back barrier layer in addition to standard field plates enabled the achievement of a remarkable three-terminal breakdown voltage V BK of over 100 V together with a power gain f max above 200 GHz for the first time on GaN devices grown on silicon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Although JFoM is more commonly cited, the f max · V B K product may be a more appropriate metric for HEMTs used in power amplifier applications, which based on a peak f max of 230 GHz is 21.8 THz· V for this study. These metrics compare well to recent reports of other vertically scaled, passivated HEMT technologies, such as AlN/GaN HEMTs grown on SiC (JFoM = 9.2 THz·V and f max · V B K = 16.8 THz·V) [15] and Si (JFoM near 10 THz·V and f max ·V B K over 20 THz·V) [16].…”
Section: Resultssupporting
confidence: 80%
“…Although JFoM is more commonly cited, the f max · V B K product may be a more appropriate metric for HEMTs used in power amplifier applications, which based on a peak f max of 230 GHz is 21.8 THz· V for this study. These metrics compare well to recent reports of other vertically scaled, passivated HEMT technologies, such as AlN/GaN HEMTs grown on SiC (JFoM = 9.2 THz·V and f max · V B K = 16.8 THz·V) [15] and Si (JFoM near 10 THz·V and f max ·V B K over 20 THz·V) [16].…”
Section: Resultssupporting
confidence: 80%
“…Recently, we have developed in this frame a novel technology based on an AlN/GaN/AlGaN-on-Si double heterostructure. It was demonstrated that a low leakage current, a high transconductance, and an extremely high current density can be achieved simultaneously using this double heterostructure [1][2][3][4][5]. Furthermore, as can be seen in Fig.…”
Section: Introductionmentioning
confidence: 90%
“…current [7,8]. On top of the material quality, the in situ grown SiN cap layer has been a key feature for controlling the surface parasitic leakage current and achieving high performance [9][10][11], namely by preventing the strain relaxation of the barrier layer. In this paper, we report on the high breakdown voltage in highly scaled GaN transistors grown on a silicon substrate, showing that all the above-mentioned issues can be overcome in these emerging types of devices.…”
Section: Methodsmentioning
confidence: 99%
“…In this frame, we have demonstrated the possibility of preventing gate tunneling through highly scaled Aluminum Nitride (AlN) barrier thickness (below 5 nm) by showing an extremely low gate leakage current [7,8]. On top of the material quality, the in situ grown SiN cap layer has been a key feature for controlling the surface parasitic leakage current and achieving high performance [9][10][11], namely by preventing the strain relaxation of the barrier layer.…”
Section: Introductionmentioning
confidence: 99%